Facile Synthesis of Hydrophilic Magnetic Mesoporous Silica Microspheres for Selective Enrichment of Glycopeptides and Glycans. (13th April 2021) - Liu, Yibin; Ma, Wende; He, Yanting; Chen, Zhuling; Lin, Zian
Abstract: Hydrophilic magnetic mesoporous silica microspheres with core-shell structure were prepared via a facile approach and applied as an enrichment probe for low-abundance glycopeptides and glycans from complex biological samples. The prepared mesoporous silica microspheres modified with gluconamide groups at the interior surface of mesopore channels showed more prominent features with respect to high specific surface area (490 m 2 /g), narrow pore size distribution (2.5 nm), and high saturation magnetization (23.87 emu/g), endowing them with hydrophilicity and size-exclusion selectivity. Taking these advantages of the size-exclusion and the hydrophilic interactions, the hydrophilic mesoporous magnetic microspheres exhibited specificity for glycopeptides in a digest of horseradish peroxidase. The detection limit for horseradish peroxidase was 25 fmol. In addition, the hydrophilic mesoporous magnetic microspheres were further applied to the selective enrichment of N-linked glycans from a digest of human serum. The successful application demonstrates the potential of the hydrophilic mesoporous magnetic microspheres in glycoproteomic analysis.